2012
DOI: 10.1021/ie301744d
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Solvent Extraction Scheme for the Reprocessing of Advanced Heavy Water Reactor Spent Fuel UsingN,N-Dihexyl Octanamide as Extractant

Abstract: Even though tri-n-butyl phosphate (TBP) has been the work horse for spent fuel reprocessing, some of its drawbacks are of major concern. Based on batch extraction studies, our group at Radiochemistry Division, BARC has proposed N,N-dihexyl octanamide (DHOA) as an alternative extractant to TBP for the reprocessing of three component Advanced Heavy Water Reactor (AHWR) spent fuels. To validate the batch data, twelve stage counter-current mixer settler runs were carried out on a simulated AHWR feed [∼2 g/L U + ∼2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…10 Similarly, the solvent extraction studies using DHOA suggested that the dialkylamides can be used as an extractant for the reprocessing of Th-based advanced heavy water reactor (AHWR) spent fuels. 5,6,11 This offers better extraction of U(VI) and Pu(IV) over Th(IV) from nitric acid medium. Even though the use of DHOA for reprocessing of Uand Th-based spent fuels appears to be promising, there is a need to investigate its preference for Pu(IV) over U(VI) (for U-based feed solutions) and for U(VI) and Pu(IV) over Th(IV) (for AHWR feed solutions).…”
Section: Introductionmentioning
confidence: 99%
“…10 Similarly, the solvent extraction studies using DHOA suggested that the dialkylamides can be used as an extractant for the reprocessing of Th-based advanced heavy water reactor (AHWR) spent fuels. 5,6,11 This offers better extraction of U(VI) and Pu(IV) over Th(IV) from nitric acid medium. Even though the use of DHOA for reprocessing of Uand Th-based spent fuels appears to be promising, there is a need to investigate its preference for Pu(IV) over U(VI) (for U-based feed solutions) and for U(VI) and Pu(IV) over Th(IV) (for AHWR feed solutions).…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Among the dialkyl amides, di-n-hexyl octanamide (DHOA, Fig. 1) has been found to be particularly interesting due to its favorable extraction properties visà-vis TBP and several recent countercurrent extraction studies underline its potential [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…13−16 Based on extensive studies, straight chain N,N-dihexyl octanamide (DHOA) was identified as an alternative of TBP for selective recovery of U and Pu from three-component (U, Pu, and Th) Advanced Heavy Water Reactor (AHWR) spent fuel dissolver solutions. 17,18 In addition, studies were also carried out to optimize the conditions for the recovery of ∼100 g/L (0.431 M) Th(IV) from AHWR raffinate solutions. 19 During Th recovery, thirdphase formation studies are of interest in view of the large concentrations of Th(IV) in the raffinate solutions.…”
Section: Introductionmentioning
confidence: 99%
“…These problems are of particular concern for the reprocessing of short-cooled fast reactor and thorium-based spent fuels. , In view of these limitations, studies have been carried out on identifying alternative extractants of TBP to alleviate at least some of these problems. In this context, N,N -dialkyl amides have been identified as promising alternatives of TBP for spent fuel reprocessing. Based on extensive studies, straight chain N,N -dihexyl octanamide (DHOA) was identified as an alternative of TBP for selective recovery of U and Pu from three-component (U, Pu, and Th) Advanced Heavy Water Reactor (AHWR) spent fuel dissolver solutions. , In addition, studies were also carried out to optimize the conditions for the recovery of ∼100 g/L (0.431 M) Th(IV) from AHWR raffinate solutions . During Th recovery, third-phase formation studies are of interest in view of the large concentrations of Th(IV) in the raffinate solutions.…”
Section: Introductionmentioning
confidence: 99%